Meningkatkan Kreativitas Guru Melalui Kepemimpinan Transformasional Kepala Sekolah. - efran; Sumarsih (UNIVERSITAS BENGKULU, 2025)
The aim of this research is to describe the implementation of the principal's transformational leadership in increasing teacher learning creativity at Yunior high school Muara Lakitan, Musi Rawas Regency. Researchers used a qualitative descriptive approach. Data collection methods use observation, interviews, documentation. Data were analyzed using an interactive model method with stages of data reduction, data presentation, verification and drawing conclusions. The results of the research show that the principal has confidence in creating school programs to realize the school's vision and mission and can be confident that he and teachers can innovate in implementing the independent curriculum. The individual consideration carried out by the school principal accepts ideas and facilitates teachers to be creative in learning by providing media and learning materials, computers, lcd, WiFi, adding to the library collection. The principal motivates teachers to practice creativity in learning by forming a teacher learning community, sharing good practices with colleagues and providing examples of cultivating the value of discipline in work, and the principal gives teachers the opportunity to design creative learning media and compete in them, conducting teacher creativity assessments. and giving awards to creative teachers.